2006
DOI: 10.1080/15376520500195566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Phosmet on Fur Residue and Cholinesterase Activity of Dogs

Abstract: Fleas, ticks, and mites are a major problem in many areas of the country for pet owners, and one treatment option involves the use of dips that contain pesticides. In the present study, dogs were dipped with a commercial phosmet (Imidan(R)) flea dip using the recommended guidelines for four consecutive treatments to determine the residues available for transfer to humans from the fur of the dogs. Twenty-four dogs of various breeds and weights were dipped, and each animal's fur was sampled with cotton gloves by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Previous reproducibility tests performed in our laboratory have shown that the decrease in CP residues on gloves with time is a result of decline by degradation or wear and is not the result of removal by the sampling procedures (Boone et al, 2001(Boone et al, , 2006. These data show that the use of cotton gloves and tee shirts for monitoring transferable residues yields reproducible results and that they do not remove appreciable amounts of the insecticide available for exposure.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous reproducibility tests performed in our laboratory have shown that the decrease in CP residues on gloves with time is a result of decline by degradation or wear and is not the result of removal by the sampling procedures (Boone et al, 2001(Boone et al, , 2006. These data show that the use of cotton gloves and tee shirts for monitoring transferable residues yields reproducible results and that they do not remove appreciable amounts of the insecticide available for exposure.…”
Section: Discussionsupporting
confidence: 55%
“…Potential exposure has been reported from pets tracking residues into a home after diazinon application to a lawn (Morgan et al, 2001). Our laboratories have also reported transferable residues of CP and phosmet from the fur of pets following an insecticide dip (Boone et al, 2001(Boone et al, , 2006.…”
Section: Introductionmentioning
confidence: 63%
“…Pesticide exposures to infants and children from food, water, and residential sources have been well documented (Woody, 1984;Zwiener and Ginsburg, 1988;Fenske et al, 1990;Morgan et al, 2001;Castorina et al, 2003;Colt et al, 2003;Rohrer et al, 2003;Hore et al, 2005;Boone et al, 2006;Chambers et al, 2007). However, one area that does not seem to have been appreciably explored is the possibility that residues of insecticides remaining on pet fur from flea control treatments could be a significant source of pesticide exposure in children.…”
Section: Introductionmentioning
confidence: 99%
“…Residues accumulated on gloves dissipated from 971 µg chlorpyrifos at 4h to 26 µg after three weeks. Boone et al [21] later conducted similar dog dipping studies with phosmet. Experimental differences in transferable residue levels were attributed to fur saturation of the dogs during dipping and rubbing pressure among the samplers.…”
Section: Discussionmentioning
confidence: 94%
“…In either case, the commercial dipping using these organophosphorous insecticides was not associated with substantial exposure (indicated by anticholinesterase activity). The amounts of organophosphorous insecticides applied during commercial dipping [1,21,22] were likely much greater than applications made by participants in our present pilot studies in which the dogs were treated by pet owners at their private residences using over-the-counter products.…”
Section: Discussionmentioning
confidence: 94%